Enlightenment ebook A novel. - Perry, Sarah (2024)
A BEST BOOK OF THE YEAR: NPR, Telegraph, Washington Post, The New Yorker. LONGLISTED FOR THE BOOKER PRIZE. "Like A.S. Byatt's Possession, Enlightenment is a baroque, genre-bending novel of ideas, ghosts and hidden histories. A richly layered epic....a heartfelt paean to the consolations of the sublime, where religion and science meet." — Telegraph "Read it, then read it again. This is a book full of unexpected wonders." — Literary Review From the author of The Essex Serpent, a dazzling novel of love and astronomy told over the course of twenty years through the lives of two improbable best friends. Thomas Hart and Grace Macaulay have lived all their lives in the small Essex town of Aldleigh. Though separated in age by three decades, the pair are kindred spirits—torn between their commitment to religion and their desire to explore the world beyond their small Baptist community. It is two romantic relationships that will rend their friendship, and in the wake of this rupture, Thomas develops an obsession with a vanished nineteenth-century astronomer said to haunt a nearby manor, and Grace flees Aldleigh entirely for London. Over the course of twenty years, by coincidence and design, Thomas and Grace will find their lives brought back into orbit as the mystery of the vanished astronomer unfolds into a devastating tale of love and scientific pursuit. Thomas and Grace will ask themselves what it means to love and be loved, what is fixed and what is mutable, how much of our fate is predestined and written in the stars, and whether they can find their way back to each other. A thrillingly ambitious novel of friendship, faith, and unrequited love, rich in symmetry and symbolism, Enlightenment is a shimmering wonder of a book and Sarah Perry's finest work to date.